2022
DOI: 10.1039/d1sm01689j
|View full text |Cite
|
Sign up to set email alerts
|

Understanding slow compression and decompression of frictionless soft granular matter by network analysis

Abstract: The evolution of dense granular systems under slow deformation is explained by network analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Inter-particle gaps between nearest neighbors are also crucial and affect the stochastic evolution of the PDFs of forces. Recently, Luding et al 20 studied the contact and force networks of frictionless soft granular materials, revealing that the evolution of the pressure in the system was correlated with the existence of loops formed in the force network during particle rearrangements. Go ¨tz et al 21 observed that soft particles with larger deformations and increased contact areas result in larger frictional forces and improved holding capacity of a granular gripper.…”
Section: Introductionmentioning
confidence: 99%
“…Inter-particle gaps between nearest neighbors are also crucial and affect the stochastic evolution of the PDFs of forces. Recently, Luding et al 20 studied the contact and force networks of frictionless soft granular materials, revealing that the evolution of the pressure in the system was correlated with the existence of loops formed in the force network during particle rearrangements. Go ¨tz et al 21 observed that soft particles with larger deformations and increased contact areas result in larger frictional forces and improved holding capacity of a granular gripper.…”
Section: Introductionmentioning
confidence: 99%
“…How and why they achieve this transition is still under debate, e.g., by irreversible plastic deformations [16][17][18][19][20][21][22][23][24][25], related also to creep/relaxation [11,[26][27][28], and many other studies, see Ref. [29] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we look closer to isotropic compression-over a wide density window, as relevant for soft particles-for moderate-to-veryslow compression rates and for various system sizes. A complementing study involved network analysis by persistence diagrams [35], and related results for frictional spheres are (to be) published elsewhere [29].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, the interactions between the particles have been extensively analyzed by using methods based on photoelasticity. 10,[18][19][20][21][22][23] Complementary information can be obtained for a wide variety of systems [24][25][26][27][28][29][30][31] by simulations based on discrete element methods. Therefore, a significant amount of research has been carried out and here we mention only a few examples.…”
Section: Introductionmentioning
confidence: 99%